2020
DOI: 10.3390/nu12061576
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Management in Chronic Liver Diseases and Hepatocellular Carcinoma

Abstract: Chronic viral hepatitis B and C and non-alcoholic fatty liver disease (NAFLD) have been widely acknowledged to be the leading causes of liver cirrhosis and hepatocellular carcinoma. As anti-viral treatment progresses, the impact of NAFLD is increasing. NAFLD can coexist with chronic viral hepatitis and exacerbate its progression. Oxidative stress has been recognized as a chronic liver disease progression-related and cancer-initiating stress response. However, there are still many unresolved issues concerning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 151 publications
(157 reference statements)
1
52
0
Order By: Relevance
“…Our results show that TGF-secretion by tumor cells could be in part responsible for activating stellate cells and for inducing the IRE1α-branch of the UPR. However, this seems to depend on the cell lines used, as the effect was not seen in the LX2 and (66,67). Therefore, an IRE1α-mediated regulation of ROS-generation might be a contributing factor that explains our findings on stellate cell activation and tumor cell proliferation after inhibiting IRE1α with 4μ8C or transfection.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results show that TGF-secretion by tumor cells could be in part responsible for activating stellate cells and for inducing the IRE1α-branch of the UPR. However, this seems to depend on the cell lines used, as the effect was not seen in the LX2 and (66,67). Therefore, an IRE1α-mediated regulation of ROS-generation might be a contributing factor that explains our findings on stellate cell activation and tumor cell proliferation after inhibiting IRE1α with 4μ8C or transfection.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, ROS is one of the critical mediators of stellate cell activation and ECM-production ( Kong et al, 2019 ). Oxidative stress has been recognized as one of the key factors in the pathogenesis of HCC and treatment strategies aiming at controlling oxidative stress have shown promising pre-clinical results ( Takaki and Yamamoto, 2015 ; Uchida et al, 2020 ). Therefore, an IRE1α-mediated regulation of ROS-generation might be a contributing factor that explains our findings on stellate cell activation and tumor cell proliferation after inhibiting IRE1α with 4μ8C or transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis has been related to oxidative stress [ 26 , 27 ]. For this reason, we checked the MDA levels and the activity of antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress has been recognized as a critical factor in the progression of many chronic liver diseases, including liver fibrosis [ 26 , 27 ]. ROS can disturb liver-specific cells’ functionality and, therefore, contribute to the development of liver fibrosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative production of ROS/RNS through either endogenous or exogenous insults is titled oxidative stress (OS) and is popular for numerous types of cancer cells that are connected with altered redox organization of cellular signaling paths. OS prompts a cellular redox imbalance that has been found to be present in different cancer cells as compared with normal cells; the redox imbalance thus may be linked to oncogenic inducement [7]. CCl 4 is an industrial chemical found in refrigerants and solvents for waxes, varnishes and other materials.…”
Section: Introductionmentioning
confidence: 99%